FAKTOR-FAKTOR YANG MEMENGARUHI PERMINTAAN BUAH ANGGUR IMPOR STUDI KASUS PASAR MODEREN (HYPERMART) DI KOTA PALU - wijaya, Indra agung; Effendy, Effendy; Damayanti, Lien (AGROTEKBIS, 2019)
This study aimed to determine the factors that affect the demand for imported grapes of modern market  (case study at Hypermart of Palu). The study was conducted from August 2017 to October 2017. The respondents' determination was conducted using accidental sampling to select 30 respondents of  imported grape consumers. The Multiple Linear Regression was employed by using F (Simultant) test and t test (Partial). The F test results showed  that the value of F-count was 24.716>F-table (2,960) indicating that simulataneously all variables including age (X1), consumer income (X2), and imported grape price (X3 ) had significant effect on the demand of  the imported grapes. The result of t test indicated that the age (X1) and the imported grape (X3) partially  had significant effect on the imported grape demand with the significance value of less 5% whereas the consumer income (X2 ) had the significance value of greater than 5%, therefore, its effect was insignificant.